2006
DOI: 10.2307/20445339
|View full text |Cite
|
Sign up to set email alerts
|

Does Stimulus Appearance Affect Learning?

Abstract: We examined the learning process with 3 sets of stimuli that have identical symbolic structure but differ in appearance (meaningless letter strings, arrangements of geometric shapes, and sequences of cities). One hypothesis is that the learning process aims to encode symbolic regularity in the same way, largely regardless of appearance. Another is that different types of stimuli bias the learning process to operate in different ways. Using the experimental paradigm of artificial grammar learning, we provided a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 65 publications
(96 reference statements)
1
27
0
1
Order By: Relevance
“…It has to be noted at this point that, at least in adult research, there is evidence that performance with such stimuli is equivalent to performance with standard AGL stimuli (Pothos, Chater, & Ziori, 2006; see also, Pothos & Kirk, 2004). The sequences of shapes were composed of between two and five elements.…”
Section: Methodsmentioning
confidence: 99%
“…It has to be noted at this point that, at least in adult research, there is evidence that performance with such stimuli is equivalent to performance with standard AGL stimuli (Pothos, Chater, & Ziori, 2006; see also, Pothos & Kirk, 2004). The sequences of shapes were composed of between two and five elements.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Chang and Knowlton (2004) showed that changing the font affected how well participants could learn the statistical patterns in the letter strings, suggesting that their knowledge was at least partly based on stimulus-specific features of the input. On the other hand, Pothos and Bailey (2000) compared AGL for embedded geometric shapes versus geometric shapes presented in sequence, and found no differences (see also , Pothos, Chater, & Ziori, 2006). In sum, the existing data is unclear regarding the specific role that input type and sensory modality play in constraining learning; specifically, how temporal and spatial constraints interact with visual and auditory implicit statistical learning has been relatively unexplored.…”
Section: Modality Effects In Statistical Learning 563mentioning
confidence: 99%
“… Pothos and Bailey (2001) andPothos et al (2006) did compare visual implicit learning using several different types of presentation formats and found no effects on learning. However, all formats consisted of visual regularities that were spatially distributed; there were no conditions examining temporally distributed regularities or auditory input.…”
mentioning
confidence: 99%
“…First, there is quite a lot of evidence that all learning in AGL takes place in training and not in test (this has been shown, for example, by AGL procedures in which there are two testing blocks; cf. Pothos et al, 2006;Redington & Chater, 1996). Accordingly, AGL can be broadly understood as a categorization task.…”
Section: Introductionmentioning
confidence: 99%